EPIDEMIOLOGICAL PROFILE OF VENOUS THROMBOSIS IN ANÁPOLIS-GO: ANALYSIS OF DATASUS DATA (2010-2024) (CIPEEX, 2025)
INTRODUCTION: Venous thrombosis is a serious condition associated with pulmonary embolism (PE) and post-thrombotic syndrome, requiring timely diagnosis and management. It affects approximately 2 per 1,000 individuals annually, with a recurrence rate of up to 25%. Between 2012 and 2022, over 425,000 Brazilians were hospitalized for venous thrombosis. In Brazil, DATASUS data guide clinical decisions and public health policy. OBJECTIVES: This study characterizes the epidemiological profile of venous thrombosis in Anápolis-GO (2010-2014) using DATASUS data, providing evidence for public health policy and clinical management. METHODS: This observational study analyzed secondary data from DATASUS, focusing on SIH/SUS (hospitalizations) and SIM (mortality). Since venous thrombosis is not a compulsory notifiable disease in Brazil, SINAN was not a primary source for DVT, except for local reporting. Variables analyzed included year, sex, age group, education level and outcome (discharge /death). Data were extracted via TabNet, and descriptive analyses were performed (frequencies and proportions). As the study used public, anonymized data, it complies with the Brazilian National Health Council Resolution CNS nº 510/2016. RESULTS: A rising temporal trend in notification is anticipated, with higher incidence among adults, predominantly women. Hospitalization for VT in SUS are substantial, underscoring the urgent need for early diagnosis, structured care pathways, and prompt clinical intervention in high-risk groups. CONCLUSION: The findings align with current guidelines. Training of healthcare professionals, and integration of vascular care pathways are recommended. Local epidemiological characterization of vein thrombosis using DATASUS data can inform prevention, early diagnosis and clinical management, improving patient safety and healthcare system efficiency.
Keywords: Deep Vein Thrombosis; Postthrombotic Syndrome; Pulmonary Embolism; Venous Thrombosis